The Involvement and Manifestations of SARS-CoV-2 Virus in Cardiovascular Pathology - Sofia Teodora Hărșan; Anca Ileana Sin (Medicina)
Although the acute phase of the COVID-19 pandemic has subsided, the emergence of the post-COVID-19 condition presents a new and complex public health challenge, characterized by persistent, multisystem symptoms that can endure for weeks or months after the initial infection with the SARS-CoV-2 virus, significantly affecting survivors’ quality of life. Among the most concerning sequelae are cardiovascular complications, which encompass a broad spectrum of conditions, including arrhythmias, myocardial damage, or postural orthostatic tachycardia syndrome. This narrative review explores the burden of the SARS-CoV-2 infection on cardiovascular health by reviewing the latest and most relevant findings in the literature and highlighting different aspects of COVID-19’s cardiovascular involvement. This review investigates the pathophysiological mechanisms underlying cardiovascular involvement in the post-COVID-19 condition, with a focus on direct viral invasion via ACE2 receptors, immune-mediated cardiovascular injury, cytokine storm, systemic inflammation, endothelial dysfunction, and mitochondrial injury. The interplay between pre-existing cardiovascular diseases, such as hypertension, atherosclerosis, diabetes, and atrial fibrillation, and COVID-19 is also explored, revealing that individuals with such conditions are at heightened risk for both severe acute illness and long-term complications. Long-term immune activation and the persistence of viral antigens are increasingly recognized as contributors to ongoing cardiovascular damage, even in individuals with mild or asymptomatic initial infections. As the healthcare system continues to adapt to the long-term consequences of the SARS-CoV-2 pandemic, a deeper understanding of these cardiovascular manifestations is essential. This knowledge will inform the development of targeted strategies for prevention, clinical management, and rehabilitation of affected patients. Furthermore, the insights gained from the intersection of COVID-19 and cardiovascular health will be instrumental in shaping responses to future viral epidemics, highlighting the necessity for multidisciplinary approaches to patient care and public health preparedness.